NDC: The Generic Old-Age Pension Scheme - Marek Góra; Edward Palmer (Institute of Labor Economics (IZA), 2019)
This chapter defines a universal public pension scheme (UPPS) as a government-mandated lifecycle longevity insurance scheme that transfers individual consumption from the working years to the retirement phase of the lifecycle. It discusses the differences in four UPPS designs defined with regard to whether they are defined contribution (DC) or defined benefit (DB), and financial (F) or nonfinancial (N). Generally speaking, DC schemes are distinguished from DB schemes by their basic building block of individual accounts. This ensures the important design feature of transparency, the "enabler" of economic efficiency - through the effects on marginal decisions to choose formal work over informal work or leisure and to postpone retirement marginally toward the end of the working life. The chapter examines additional criteria (fairness, financial sustainability, affordability, and adequacy), plus some other design characteristics of interest in a comparative assessment. The conclusion is that the two UPPS-DC designs are superior to the two UPPS-DB designs. The difference in the relative rates of return of NDC versus FDC designs, together with uncertain demographic effects on future investment needs, speak in favor of a UPPS portfolio with both. UPPS-FDC involves additional risks and costs, but also provides positive effects through returns for individuals and the economy.
Keywords: D6; D62; D81; E62; G22; G28; H23; H55; J14; J18; 330; non-financial defined contribution (NDC); income allocation; retirement; externalities; transparency; fairness; universal public pension scheme (UPPS)